Opinion Mining Algorithm Based on the Evaluation of Online Mathematics Course with Python - Huang, Yunpeng (2021 5th International Conference on Electronics, Communication and Aerospace Technology (ICECA), 2021)
Opinion mining algorithm based on the evaluation of the online mathematics course with Python is designed and implemented in this study. Natural language is the language used by humans to communicate. When using natural language, it can more or less always leave the user's subjective view of people, things and things. Therefore, texts with subjective content are widely present in our lives. Hence, in this paper, the data mining and the pattern recognition models are used to construct the model. The Python is used and optimized for the systematic design. The framework is simulated on different datasets, the performance is well validated.